Pola Asuh Grandparenting dalam Membentuk Kepribadian Anak Usia Dini di Desa Jati Alun-Alun Kecamatan Prambon Kabupaten Sidoarjo - Kurnia Dewi Larasati; Gunarti Dwi Lestari (J+PLUS UNESA, 2023)
Grandparenting is a parenting method carried out by grandparents. Actually in the family, parents are responsible for raising and educating their children. This study aims to describe the grandparenting style in improving the personality of early childhood in Jati Alun-Alun Village. This study uses a qualitative descriptive approach. Data collection was carried out using interviews, observation, and documentation. Then the data were analyzed using data collection, data condensation, data presentation, verification and conclusion. The results showed that (1) Grandparenting in Jati Alun-Alun Village mostly applied democratic parenting (2) Efforts made by grandparenting in shaping the personality of early childhood used several methods, namely instilling moral and religious values , applying discipline, giving reprimands and praise, helping children solve problems, and giving time for children (3) Obstacles faced by grandparenting in shaping the personality of early childhood in Jati Alun-Alun Village are conflicts between grandparenting and children's parents, age factor , and environmental factors.